SARS-CoV-2: Molecular Structure, Pathogenesis, Potential Therapeutic Targets, and Immune Response of the Infected Subject - Wumba, R.; Mandina, M.; Nlandu, Y.; Makulo, J. R.; Tshimpi, A.; Mbala, P.; Mbangama, A.; Kabututu, P.; Kayembe, J. M. (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. The pathogenic mechanisms and immune response of COVID-19 are far from clear. Through a documentary review of literature, the authors describe virological and molecular aspects of SARS-CoV-2, the intimate mechanisms of cell infection, and potential therapeutic targets. They also analyze the characteristics of immune response of the infected subject. Objectives. Objectives of this study are to describe the state of knowledge on virological data, molecular and physiopathogenic mechanisms of SARS-CoV-2, with a view to a better understanding of the therapeutic targets, as well as the immune response of the infected subject. Methodology. This documentary review is a compilation of several meta-analyses, consistent with the methodology described in the PRISMA statement on literature data on SARS-CoV-2, published between March 22 and August 14, 2020 (Moher et al.). The search engines used for the selection of articles were as follows: PubMed, Google Scholar, Global Health, and WHO reports. Papers of interest were those addressing virological and molecular data on SARS-CoV-2, therapeutic aspects of COVID-19, and immunity of the infected subject. Of the 617 eligible papers, 417 could be retained after removing the duplicates. Ultimately, only 50 articles were retained for final evaluation. The data collected allowed the development of a two-armed model around the physiopathological aspects and potential therapeutic targets, as well as aspects of host immunity, respectively. The model was then compared to data from the HIV literature. Conclusion. Reported data could contribute to a better understanding of molecular mechanisms of cellular infection by SARS-CoV-2 as well as to a more easy explanation of the action of pharmacological agents used for the treatment, while elucidating intimate mechanisms of the immunity of infected subject.